Pedagogy in Basic and Higher Education Current Developments and Challenges - Tirri, Kirsi; Toom, Auli (IntechOpen, 2020)
This book takes a holistic approach to pedagogy and argues that the purpose of education is to educate the student's whole personality including cognitive, social, and moral domains. The four sections and twelve chapters address the current pedagogical challenges in basic and higher education in international contexts. The authors describe the principles and practices through which meaningful education is promoted and enhanced in a variety of ways. The challenges educators face in their profession as well as ways to overcome them are elaborated on both theoretically and empirically. The book allows both researchers, teachers, and educational policy makers to reflect on current developments, challenges, and areas of development in educational institutions when aiming to support student growth and learning.